Highly stereoselective spirocyclopropanation of various diazooxindoles with olefins catalyzed using Ru(ii)-complex. Issue 70 (28th November 2018) - Tone, Masaya; Nakagawa, Yoko; Chanthamath, Soda; Fujisawa, Ikuhide; Nakayama, Naofumi; Goto, Hitoshi; Shibatomi, Kazutaka; Iwasa, Seiji
Abstract : Optically active spirocyclopropyloxindole derivatives were efficiently synthesized from diazooxindoles and olefins in the presence of a Ru(ii )-Pheox catalyst. Abstract : Optically active spirocyclopropyloxindole derivatives were efficiently synthesized from diazooxindoles and olefins in the presence of a Ru(ii )-Pheox catalyst. Among a series of Ru(ii )-Pheox catalysts, Ru(ii )-Pheox6e was determined to be the best catalyst for spirocyclopropanation reactions of diazooxindoles with various olefins in high yields (up to 98%) with high diastereoselectivities (up to trans : cis = >99:1<) and enantioselectivities (up to 99% ee). Furthermore, as the first catalytic asymmetric synthesis, anti-HIV active candidate4a and a bioactive compound of AMPK modulator4c were easily synthesized from the corresponding diazooxindoles1i and1b, respectively, in high yields with high enantioselectivities (4a : 82% yield, 95% ee, 4b : 99% yield, 93% ee).